VO2 kinetics during heavy and severe exercise in swimming - Pessoa Filho, D. M.; Alves, F. B.; Reis, J. F.; Greco, C. C.; Denadai, B. S. (International Journal of Sports Medicine, 2012)
The purpose of this study was to describe the VO2 kinetics above and below respiratory compensation point (RCP) during swimming. After determination of the gas-exchange threshold (GET), RCP and VO2max, 9 well-trained swimmers (21.0±7.1 year, VO2max=57.9±5.1 ml.kg - 1.min - 1), completed a series of "square-wave" swimming transitions to a speed corresponding to 2.5% below (S - 2.5%) and 2.5% above (S+2.5%) the speed observed at RCP for the determination of pulmonary VO2 kinetics. The trial below (~2.7%) and above RCP (~2%) was performed at 1.28±0.05 m.s - 1 (76.5±6.3% VO2max) and 1.34 0.05 m.s - 1 (91.3±4.0% VO2max), respectively. The time constant of the primary component was not different between the trials below (17.8±5.9 s) and above RCP (16.5±5.1 s). The amplitude of the VO2 slow component was similar between the exercise intensities performed around RCP (S - 2.5%=329.2±152.6 ml.min - 1 vs. S+2.5%=313.7±285.2 ml.min - 1), but VO2max was attained only during trial performed above RCP (S-2.5%=91.4±5.9% VO2max vs. S+2.5%=103.0±8.2% VO2max). Thus, similar to the critical power during cycling exercise, the RCP appears to represent a physiological boundary that dictates whether VO2 kinetics is characteristic of heavy- or severe-intensity exercise during swimming.